Peran Keputusan Kuliah dalam Memediasi Pengaruh Citra Perguruan Tinggi dan Dukungan Keluarga Terhadap Keberlanjutan Perguruan Tinggi - Masduki Masduki; Endah Prihartini; Alan Rusdiana; Dudung Abdullah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
The sustainability of a tertiary institution can be seen from various perspectives, one of which is the customer aspect. Based on the customer perspective, in this case students, universities will have sustainable competitiveness when considering the number of students who decide to study at these universities. Therefore it is important to pay attention to the factors that influence college decisions which will have an impact on the sustainability of higher education. This study aims to examine the role of college decisions in mediating the influence of college image and family support on college sustainability. This type of research is associated with the survey method. The population in this study were all students of Majalengka University. While the sample in this study were 155 students at Majalengka University. The data analysis method uses SEM with the help of the AMOS 21 application. The results show that the image of a university and family support have a positive effect on college decisions. Then the image of the university and the decision to study directly have a positive effect on the sustainability of the university. An important finding in this research is that college decisions mediate the influence of college image and family support on college sustainability.